Turkish Teachers’ Awareness and Perceptions of Open Educational Resources - Ozgur Ozdemir (Commonwealth of Learning, 2017)
The purpose of this study is to explore K-12 teachers’ awareness of open educational resources (OER) as well as their perceptions of its potential opportunities and challenges for teaching practices. Data were gathered from 99 online survey respondents and six interviewees in this study. Findings showed that teachers are aware of OER to a certain degree; however, a misunderstanding exists between digital educational content on the Internet and openly licensed content compatible with the OER definition. Lack of knowledge regarding licensing mechanisms of OER is a major issue among teachers. Whereas, teacher perceptions that the use of OER leads to the improvement in student performance is highly beneficial, the time required to search, select, edit, and apply OER was discovered as the greatest challenge to OER utilization. Results of this study can inform potential OER movement contributors, such as teacher professional development specialists, developers of OER repositories, and academics interested in OER.